Coastal landuse land cover change and transformations in-between Cuddalore and Nagore, south east coast of India using remote sensing and GIS - Thangaraj, Kongeswaran; Karthikeyan, Sivakumar; Arumugam , Muruganantham; Kulandaisamy, Prabakaran; Velmayil , Perumal; Vellaikannu , Agastheeswaran; Sundaram , Bangaru Priyanga; Rajendran, Muthuramalingam (Acta Geographica Debrecina Landscape & Environment series, 2025)
This study was conducted to assess the Land use and land cover (LULC) changes in a dynamic coastal zone; this is also an essential factor of studying the relationships between the human activity and coastal environment. The study region has been suffered from various natural hazards such as cyclone impacts, coastal erosion and rarely tsunamis. LULC changes was studied and reported for the period of 4 decades from 1980 to 2020. The overall accuracy assessment and Kappa coefficient values shows the substantial results of LULC maps. In the study area LULC changes has been classified in the six classes. The result shows reduction in plantations, coastal wetland and fallow land. Whereas improvement found in barren land, built-up land and water body of the study area from 1980 to 2020. Immediate attention is required to the increase the mangrove forest to be as a natural protection from the calamities in coastal wetlands. The information resulting from this study can be used in forthcoming management plans for urbanization and towards the sustainable development of the region. This study can be adapted to the world’s any coastal region to establish a strategic plan of action to protect the coastal communities and the environment.